التجربة الألمانية في اقتصاد السوق الاجتماعي الأسس والمبادئ النظرية - هرمز, نور الدين; سلامة, باسل (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يناقش البحث بنية ومصادر اقتصاد السوق الاجتماعي في ألمانيا، على اعتبار أن هذه التجربة من أهم التجارب العملية في تطبيقه، وذلك من خلال عرض الفكرة الأولى لظهوره في ألمانيا، والجذور والمصادر التي انبثقت منها وتطورت من خلالها، وبالتالي التعرف على الأسس والمرتكزات الأساسية التي يقوم عليها هذا المفهوم، ومن ثم التعرف على الهيكل المؤسساتي الذي طبق من خلاله، والتعرف على دور الدولة في تنفيذ وتطبيق اقتصاد السوق الاجتماعي، من أجل الاستفادة منه في سورية. The paper discusses the structure and sources of social market economy in Germany, on the grounds that this experience is the most important practical experience in its application, and that through the presentation of the idea first appeared in Germany and the roots and sources which were founded through them, and thus to identify the foundations and the basic pillars on which this concept stand, and then to identify the institutional structure which has been applied, and it also recognized the state's role in implementing and applying the social market economy, in order to take advantage of it in Syria.